‘THEY SAY ISLAM HAS A SOLUTION FOR EVERYTHING, SO WHY ARE THERE NO GUIDELINES FOR THIS?’ ETHICAL DILEMMAS ASSOCIATED WITH THE BIRTHS AND DEATHS OF INFANTS WITH FATAL ABNORMALITIES FROM A SMALL SAMPLE OF PAKISTANI MUSLIM COUPLES IN BRITAIN - Shaw, Alison (Bioethics, 2012)
This paper presents ethical dilemmas concerning the termination of pregnancy, the management of childbirth, and the withdrawal of life-support from infants in special care, for a small sample of British Pakistani Muslim parents of babies diagnosed with fatal abnormalities. Case studies illustrating these dilemmas are taken from a qualitative study of 66 families of Pakistani origin referred to a genetics clinic in Southern England. The paper shows how parents negotiated between the authoritative knowledge of their doctors, religious experts, and senior family members in response to the ethical dilemmas they faced. There was little knowledge or open discussion of the view that Islam permits the termination of pregnancy for serious or fatal abnormality within 120 days and there was considerable disquiet over the idea of ending a pregnancy. For some parents, whether their newborn baby would draw breath was a main worry, with implications for the baby's Muslim identity and for the recognition of loss the parents would receive from family and community. This concern sometimes conflicted with doctors' concerns to minimize risk to future pregnancies by not performing a Caesarean delivery if a baby is sure to die. The paper also identifies parents' concerns and feelings of wrong-doing regarding the withdrawal of artificial life-support from infants with multiple abnormalities. The conclusion considers some of the implications of these observations for the counselling and support of Muslim parents following the pre- or neo-natal diagnosis of fatal abnormalities in their children.